Pengembangan Bahan Ajar Teks Deskripsi Berbantuan Aplikasi Filmorago Pada Siswa Kelas VII SMP Swasta Musyawarah Perbulan - Anita Khairani Dalimunthe; Syamsul Arif (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2024)
This study aims to describe the stages of development and feasibility of teaching materials assisted by the Filmorago application for class VII description text material. The use of the Borg and Gall model in this study modified by Sugiyono, namely through the potential and problem analysis stage, data collection, product design, design validation, revision and trial stage. The validation stage included material expert lecturers and media expert lecturers to evaluate the feasibility of the material and the feasibility of the media. The sample of this study was 31 students of class VII of SMP Swasta Musyawarah Perbulan. Data collection techniques with interviews and questionnaires. The research instrument is a questionnaire sheet for validation of material experts and media experts using Likert scale calculations. Data analysis using qualitative descriptive analysis. The research shows that the product of the teaching material for description text assisted by the Filmorago application gets research results with the criteria "Very Good" with an average of 90%, with the results of the material expert validator of 85% with Very Good criteria" As well as the results of the media expert validator of 90% with the criteria "Very Good" The results of the product trial received a score from the teacher of 96% with the criteria "Very Good" and a student assessment of 90% with the criteria "Very Good". Therefore, class VII description text-assisted teaching materials are very feasible to use in learning.